`Grant Wood : artist in overalls - Duggleby, John . (San Francisco, CA : Chronicle Books, 1996)
Follows the life of the Iowa farm boy who struggled to realize his talents and who painted in Paris but returned home to focus on the land and people he knew best.
Keywords: Wood, Grant, -- 1891-1942 -- Juvenile literature; Wood, Grant, -- 1891-1942.; Painters -- United States -- Biography -- Juvenile literature; Artists